PENINGKATAN HASIL BELAJAR SISWA MATERI LINGKUNGAN FISIK DAN PERUBAHANNYA KELAS IV MIM 06 BRONDONG-LAMONGAN MELALUI CONTEXTUAL TEACHING AND LEARNING (CTL) - Anggun Winata; Nur Aini (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2016)
This research is motivated by a lack of class IV student learning outcomes in learning science at MIM-06 Brondong Lamongan. Teachers only do conventional learning, so that students more easily bored and not interested in the material that is taught. Therefore, in order to be able to increase student learning outcomes, the need for learning to create an atmosphere of learning interesting and fun. The purpose of this research is to improve student learning outcomes and physical environmental material amendments fourth grade MIM 06 Brondong- Lamongan through Contextual Teaching And Learning (CTL). This research is the Classroom Action Research (CAR) conducted in two cycles, with each cycle consisting of four phases of activity: (1) planning, (2) action, (3) observation, and (4) reflection. The subjects were students of class IV Mim 06 Brondong-Lamongan Semester II Academic Year of 2015/2016. The instrument used in this study are: syllabus, learning implementation plan, observation sheets, interview and evaluation sheets. Through the application of Contextual Teaching and Learning (CTL) obtaining results that completeness cognitive achievement of students has increased from cycle II (31%) and the second cycle (54%).